EXPLORING DEPERSONALIZATION TOLL ON EFL TEACHERS' WELL-BEING IN SOCIAL CONTEXTS - Zelvy Fauzan; Nur Arifah Drajati; Kristian Adi Putra (PROJECT (Professional Journal of English Education), 2024)
Relationship and interaction among teacher-student, colleague, school leader, and other workers in the school workplace is one of the building blocks of teacher well-being. Possessing positive social relationship among those parties can increase the quality of EFL teacher’s well-being. However, social dynamics in the workplace is often cause friction among those parties. This could lead to depersonalization then causing them to experience burnout, and in some cases job attrition. The nature in which burnout can contagion other EFL teacher has urged further investigation of this matter. Grounded upon narrative inquiry research method, this research fetched narrative frames from three EFL teachers who works at a public junior high school. Thematic analysis specialized for narrative inquiry research revealed that colleagues who possess negative traits in terms of professional development and work ethics as well as poor school leader characteristic are the main cause EFL teachers to experience a sense of depersonalization and motivation loss. Systemic and/or organizational level endeavors to prevent or alleviate depersonalization to maintain EFL teachers’ well-being is advised.